57.2: Electrical Characterization of BCE‐TFTs with a‐IGZTO Oxide Semiconductor Compatible with Cu and Al interconnections. Issue 1 (June 2015) - Ochi, Mototaka; Morita, Shinya; Takanashi, Yasuyuki; Tao, Hiroaki; Goto, Hiroshi; Kugimiya, Toshihiro; Kanamaru, Moriyoshi
Abstract : We have developed an amorphous In‐Ga‐Zn‐Sn‐O (a‐IGZTO) semiconducting thin film for back channel etching (BCE) type thin‐film transistors (TFTs). As the material is highly stable to acid etchants, the fabrication of the IGZTO TFTs having both Al and Cu interconnections is viable by back channel etching using conventional etchant such as PAN and H2 O2 ‐based etchants.